La difícil relación entre la curva demográfica negativa europea, la curva demográfica positiva africana y la seguridad nacional - CUENCA BUA, Francisco Javier (Journal of the Spanish Institute for Strategic Studies, 2023)
Abstract In the last thirty years, but especially in the last ten years, all governments and national authorities have developed a great interest in the lack of generational change and the negative consequences that this entails in our social fabric. The first of the aspects that tend to be listed is related to the deterioration of the pension system, but on very few occasions, it points to other aspects, more serious and that would make us understand the reason for the adoption of little applauded policies, such as immigration. Being from our point of view, the National Security factor one of the most important aspects, but still less commented. Keywords: Demographic decline, immigration, National Security.